Methods of Measuring Human Resource Costs and their Impact on The Financial Statements: (A Case study Of Kennan Sugar - حمزة بشري جمعة أبكر (White Nile Journal for Studies and Research, 2017)
تمثلت مشكلة الدراسة في غياب المنهجية السليمة لقياس قيمة الموارد البشرية على مستوى المشروع ، لذا هدفت الدراسة إلى بيان أهمية محاسبة الموارد البشرية في تحقيق أهداف المنشأة و توضيح أهم المشاكل التي تواجه عملية قياس وتقييم للموارد البشرية على مستوى المنشأة ، افترضت الدراسة وجد علاقة ذات دلالة إحصائية بين اعتبار مجمل الإنفاق على الموارد البشرية إنفاقا جارياً وعدم ظهور النفقات في القوائم المالية ، توجد علاقة ذات دلالة إحصائية بين تحقيق أهداف ومزايا قياس تكاليف الموارد البشرية وصحة بيانات القوائم المالية توصلت الدراسة إلى عدة نتائج منها : عدم الإفصاح عن الموارد البشرية بعد قصور في تحديد الربح المحاسبي في قائمة الدخل وأن اعتبار الإنفاق على الموارد البشرية إنفاق رأسمالي يؤدى إلى ظهور قائمة الدخل وبيانات غير صحيحة قياس قيمة الموارد البشرية بشكل سليم يؤدي إلى صدق ودقة بيانات القوائم المالية ، أو صى الدراسة بضرورة اعتبار الإنفاق على الموارد البشرية إنفاق جاري يحمل إلى حساب قائمة الدخل. Abstract The problem of the study is that; there is no proper basis for measuring the value of human resources at the level of the project as well? The objective of the Study is to show the importance of accounting for human resources in achieving the objectives of the establishment. Clarify the most important problems in the process of measuring and evaluating human resources at the enterprise level. The study assumes that there is a statistically significant relationship between the consideration of the total expenditure on human resources expenditure and the absence of this expenditure in the financial statements. There is a statistically significant relationship between achieving the objectives and benefits of measuring human resources costs and the validity of financial statement data. On human resources deficiency in the determination of accounting gain is recognized in the income statement. addition, expenditure on human resources is considered a capital expenditure leading to the emergence of the income statement and incorrect data. The proper measurement of the value of human resources leads to the perfection and accuracy of financial statement data, or the study should consider expenditure on human resources as current expenditure.